Newly qualified professional nurses' experiences providing postoperative care to children in CTICU - Thereza M. Mehlape; Sidwell Matlala (AOSIS, 2024)
Background: It is challenging for newly qualified professional nurses (NQPNs) to care for children with congenital heart abnormalities following cardiac surgery in cardiothoracic critical care units. This population of nurses is allocated to critically ill children in the cardiothoracic intensive care unit (CTICU) even though they lack sufficient knowledge, experience and skills to care for these patients. Objectives: This study explored, described and made recommendations to support NQPNs who provide postoperative care to children in a CTICU. Method: A qualitative, exploratory, descriptive and contextual research design was used. Purposive sampling was employed, and in-depth individual phenomenological interviews were conducted with 10 NQPNs. Data were analysed according to Giorgio's descriptive phenomenological method, and measures to ensure trustworthiness and ethical principles were followed. Results: The NQPNs cited their lack of knowledge and mentoring as the primary contributors to their perceived challenges. This population requires motivation, mentoring and empowerment to address this phenomenon. Conclusion: Professional nurses in CTICUs require a supportive work environment, with encouragement from colleagues, management and doctors. A lack of support compromises patient care outcomes and safety, resulting in litigation. Contribution: Recommendations are provided for nursing education, research and practice to empower NQPNs with knowledge and skills to work with children following cardiac surgery to avoid adverse events in the CTICU.